Workshop Creative Content Creation untuk Siswa-Siswi SMA di Padang - Rabbi Antaridha; Rahma Yanti; Yalmiadi Yalmiadi; Irsyad Shabri; Widya Fhitri; Thiska Septa Maiza; Emil Eka Putra (Jurnal Pengabdian Masyarakat Dharma Andalas, 2025)
This community service program aims to provide senior high school and vocational high school students in Padang with fundamental knowledge and skills in creative content creation, an essential competency in the digital era. Although the content creator profession has become increasingly popular due to its accessibility, many students still lack an understanding of the basic principles required to produce high-quality and effective content. Through this workshop, participants will learn about idea development, storytelling, and content creation techniques. The program also emphasizes the importance of storytelling skills as the ability to craft narratives that are engaging, relevant, and meaningful to audiences. Amid the rapid advancement of artificial intelligence (AI), the ability to tell stories in a creative and authentic manner is becoming increasingly valuable, as it cannot be fully replaced by technology. Therefore, this program is expected to enhance participants’ creativity, critical thinking skills, and readiness to face the challenges of the future digital world.